Late Corrective Arthrodesis in Nonplantigrade Diabetic Charcot Midfoot Disease Is Associated with High Complication and Reoperation Rates. (27th April 2015) - Eschler, Anica; Gradl, Georg; Wussow, Annekatrin; Mittlmeier, Thomas
Abstract : Introduction . Charcot arthropathy may lead to a loss of osteoligamentous foot architecture and consequently loss of the plantigrade alignment. In this series of patients a technique of internal corrective arthrodesis with maximum fixation strength was provided in order to lower complication rates. Materials/Methods . 21 feet with severe nonplantigrade diabetic Charcot deformity Eichenholtz stages II/III (Sanders/Frykberg II/III/IV) and reconstructive arthrodesis with medial and additional lateral column support were retrospectively enrolled. Follow-up averaged 4.0 years and included a clinical (AOFAS score/PSS), radiological, and complication analysis. Results . A mean of 2.4 complications/foot occurred, of which 1.5/foot had to be solved surgically. 76% of feet suffered from soft tissue complications; 43% suffered hardware-associated complications. Feet with only 2 out of 5 high risk criteria according to Pinzur showed significantly lower complication counts. Radiographs revealed a correct restoration of all foot axes postoperatively with superior fixation strength medially. Conclusion . Late corrective arthrodesis with medial and lateral column stabilization in the nonplantigrade stages of neuroosteoarthropathy can provide reasonable reconstruction of the foot alignment. Nonetheless, overall complication/reoperation rates were high. With separation into low/high risk criteria a helpful guide in treatment choice is provided. This trial is registered with German Clinical Trials Register (DRKS) under numberDRKS00007537 .